2015
DOI: 10.1097/mca.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trimetazidine and ranolazine on endothelial function in patients with ischemic heart disease

Abstract: Both trimetazidine and ranolazine led to an improvement in FMD and GTN of the brachial artery in patients with ischemic heart disease, with no statistically significant difference between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…Moreover, in a study by Tritto et al (), TMZ‐induced protection of contractile function in isolated rat heart during ischaemia/reperfusion was linked to inhibition of neutrophil activation, while Chen et al () detected inhibition of the macrophage‐mediated pro‐inflammatory response in mice treated with TMZ prior to endotoxin‐induced cardiomyopathy. Therefore, TMZ might also act via some extramitochondrial, or even extracardiac mechanisms, as suggested by recent studies reporting the effect of TMZ on endothelial function (Rehberger‐Likozar and Sebestjen, ) and whole body insulin sensitivity (Tuunanen et al , ). Some of these effects may, independently of metabolic modulation, confer the clinical improvements associated with TMZ therapy.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, in a study by Tritto et al (), TMZ‐induced protection of contractile function in isolated rat heart during ischaemia/reperfusion was linked to inhibition of neutrophil activation, while Chen et al () detected inhibition of the macrophage‐mediated pro‐inflammatory response in mice treated with TMZ prior to endotoxin‐induced cardiomyopathy. Therefore, TMZ might also act via some extramitochondrial, or even extracardiac mechanisms, as suggested by recent studies reporting the effect of TMZ on endothelial function (Rehberger‐Likozar and Sebestjen, ) and whole body insulin sensitivity (Tuunanen et al , ). Some of these effects may, independently of metabolic modulation, confer the clinical improvements associated with TMZ therapy.…”
Section: Discussionmentioning
confidence: 94%
“…This may be the reason why there is no difference in pain-free walking distance between the two groups of patients after treatment. Trimetazidine has been reported to be able to improve endothelial function (22), and plasmin also to be able to promote endothelial progenitor cell production, repair vascular damage and improve endothelial function (23). The results of the current study showed that the degree of improvement of the two drugs in endothelial function was similar, but all the results had not been verified.…”
Section: Discussionmentioning
confidence: 99%
“…У наших пациентов, согласно данным фотоплетизмографии в динамике, отмечалось сопоставимое улучшение струк-турно-функционального состояния крупных артерий при лечении обеими тройными комбинациями антианги-нальных препаратов. Эти данные согласуются с сообще-нием A. Rehberger-Likozar и M. Šebeštjen [31] о том, что лечение триметазидином или ранолазином в равной мере улучшает вызванную потоком и индуцированную нитроглицерином дилатацию плечевой артерии у паци-ентов с ИБС.…”
Section: ишемическая болезнь сердцаunclassified